ANALYSIS ENTERPRISE RESOURCE PLANNING (ERP) IN EMPLOYEES OF PT. GRACE TECHINC BALIKPAPAN - Erlin Setyaningsih; Hasrullah Hasrullah; Adi Hermawansyah; Nuorma Wahyuni; Dila Seltika Canta (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
The information system that can help improve the effectiveness and efficiency of work is Enterprise Resource Planning (ERP). The ERP is an information system that integrates information available in the company from the various aspects of resources. The purpose of this research is to provide an overview of the ERP-based information system for PT Grace Technic employees in influencing the implementation of working processes for all employees. The data collection is in this study was carried out through the questionnaire. The Data analysis is used qualitative analysis by distributing questionnaires to respondents, is the employees who work by calculating percentage scores. This research was conducted with the aim of knowing and analyzing the influence of ERP on employees in PT. Grace Technic Balikpapan Based on the ERP implementation data and information. The method is used the quantitative research method. The research instruments are the tools or facilities used by researchers in collecting data, so that their work is easier and the results are better, more accurate, complete and systematic. The results of this research indicate that the Enterprise Resource Planning (ERP) at PT. Grace Technic Balikpapan showed that the results are very good percentage score can help the employee in managing performance so that they can maximize the employee work and then what must be done is to develop the ERP system, in management commitment and training in the use of the ERP system.